Z problematyki wykładni prawa karnego: [Problems of interpretation of criminal law] (Studia Prawnicze / The Legal Studies, 2009)
Podjęcie problematyki wykładni w ramach szczegółowej dziedziny nauk prawnych, w tym przypadku prawa karnego wydaje się uzasadnione.W jednej ze swych publikacji E. Łętowska wyraziła ubolewanie, iż wiedzao tym, „co można zrobić z tekstem prawniczym” nie jest przedmiotemodrębnego nauczania na polskich uczelniach prawa. Nie ma tu systematycznego kursu tego, co na uczelniach niemieckich określa się jako Methodenlehre. Co gorzej, polskich adeptów prawa utrzymuje się w fałszywym przekonaniu, że jedyną godną zainteresowania jest wiedzao tekście prawa i ta właśnie wiedza jest przedmiotem nauki jako nauka „prawa”. O interpretacji adepci prawa dowiadują się przeważnie wpadkowo jako o tzw. „praktyce”, która bywa zmienna i nie zawsze zgodnaz „prawem” czyli tekstem (dlatego właśnie nie jest przedmiotem odrębnego nauczania), albo jako o nagannej „falandyzacji” prawa Techniki interpretacji jako odrębnego przedmiotu nauczania nie ma, jest to więc u nasraczej sprawą samouctwa i doświadczenia Interpretacja skazana jest na niesamodzielny żywot cienia tekstu prawa Lekceważenie zaś interpretacji prowadzi do braku świadomości warsztatu, powierzchowności wykształcenia, co owocuje przypadkowością osiąganych rezultatów - gdy idzie o stosowanie prawa Brak wiedzy „warsztatowej” czyni też nieodpornym na manipulacje i ogranicza możliwość polemiki z ewidentną nadinterpretacją Talking about “interpretation of penal law” one must be aware that none of these three words is explicit. Comprehension of “interpretation” some reffer to only those parts of low text which meaning brings doubts, the others claim, that law text whether it is clear or not, always requires an interpretation. When it comes to the interpretation of law, there are beliefs which reduce law only to the law text and there are others who claim that law is not only the law text, but it (the law) is also its interpretation. Finally, the comprehension of “penal law” is related to various areas not only to crime but also to offences, autonomic branch of tax law, so called administrative and penal law, so called juvenile law or penal law of collective subjects. The vital interpretative meaning for system reference within the limits of such vast area of material penal law has the expression of “amenability to law” the interpretation of which brings some problems for principles. The next problem arouses from the links between the penal law and extrapenal branches of law. It is defined in the question: Should the notions which appear in penal law and originate from other branches of law be given the same meaning as they have in a given branch of law or they are allowed to be interpreted independentely and autonomically according to the needs of penal law? There are three attitudes to the question:- the first one shows the concept of full dependance and unity of meaning;- the second (contrary) suggests that the notions which appear in penal law and originate from other branches of law should be interpreted to respond the functions of penal law. They should not follow the inerpretation they have in the branches of law they originate from.- the third attitude combines the two above ones. (intermediate)As a matter of fact, the source of this kind of problems with interpretation are often difficulties of the proper definiction of the subject of the penal law protection, which is supposed to show the direction of iterpretation in penal law. Beside the problem with unity of the meaning of notions in the whole system of law there is also a problem inside the same penal law directive. The problem exists because the sense of the notions used in regulations depends not only on linguistic context but also on a systematic and functional context. That is why the newest jurisdiction indicates that the interpretation process should involve all the methods of interpretation: linguistic, system and functional because relying only on the first one is insufficient. Vital issues are also connected with the notion of analogy. lt is important to define the right understunding of this notion and separate it from the notion of extensive interpretation. There should also be admitted to use analogy in penal law what is connected with the problem if it works to somebodies advantage or disadvantage.